Nowhere to room ... nobody told them’: logistical and cultural impediments to Aboriginal peoples’ participation in cancer treatment - Shahid, Shaouli; Finn, Lisabeth; Bessarab, Dawn; Thompson, Sandra (CSIRO Publishing, 2011)
Background. Cancer mortality among Indigenous Australians is higher compared to the non-Indigenous population and attributed to poor access to cancer detection, screening, treatment and support services. A large proportion of Indigenous Australians live in rural and remote areas which makes access to cancer treatment services more challenging. Factors, such as transport, accommodation, poor socio-economic status and cultural appropriateness of services also negatively affect health service access and, in turn, lead to poor cancer outcomes. Design, setting and participants. Qualitative research with 30 in-depth interviews was conducted with Aboriginal people affected by cancer from across WA, using a variety of recruitment approaches.Results. The infrastructure around the whole-of-treatment experience affected the decision-making and experiences of Aboriginal patients, particularly affecting rural residents. Issues raised included transport and accommodation problems, travel and service expenses, displacement from family, concerns about the hospital environment and lack of appropriate support persons. These factors are compounded by a range of disadvantages already experienced by Aboriginal Australians and are vital factors affecting treatment decision-making and access. Conclusion. To improve cancer outcomes for Aboriginal people, logistical, infrastructure and cultural safety issues must be addressed. One way of ensuring this could be by dedicated support to better coordinate cancer diagnostic and treatment services with primary healthcare services.